Proceedings of the Second Conference on Machine Translation 2017
DOI: 10.18653/v1/w17-4773
|View full text |Cite
|
Sign up to set email alerts
|

Multi-source Neural Automatic Post-Editing: FBK’s participation in the WMT 2017 APE shared task

Abstract: Previous phrase-based approaches to Automatic Post-editing (APE) have shown that the dependency of MT errors from the source sentence can be exploited by jointly learning from source and target information. By integrating this notion in a neural approach to the problem, we present the multi-source neural machine translation (NMT) system submitted by FBK to the WMT 2017 APE shared task. Our system implements multi-source NMT in a weighted ensemble of 8 models. The n-best hypotheses produced by this ensemble are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The translations can then be post-edited, a process that is less labor-intensive and cheaper compared to translating from scratch. Multi-source NMT has been used for post-editing where the translated sentence is used as an additional source, leading to improvements [18]. Multi-source NMT has also been used for system combination, which combines NMT and SMT outputs to improve translation performance [166].…”
Section: Multi-source Nmtmentioning
confidence: 99%
“…The translations can then be post-edited, a process that is less labor-intensive and cheaper compared to translating from scratch. Multi-source NMT has been used for post-editing where the translated sentence is used as an additional source, leading to improvements [18]. Multi-source NMT has also been used for system combination, which combines NMT and SMT outputs to improve translation performance [166].…”
Section: Multi-source Nmtmentioning
confidence: 99%
“…Our model outperforms the best performing system at the last round of the shared task (Chatterjee et al, 2017), with improvements up to -1.27 TER and +1.23 BLEU on the PBSMT development set. Although we are using more out-ofdomain data, it is interesting to note that these scores are obtained with a much simpler architecture, which does not require to ensemble n models and to train a re-ranker.…”
Section: Resultsmentioning
confidence: 88%
“…In the last few years, the APE shared tasks at WMT (Bojar et al, 2015(Bojar et al, , 2016(Bojar et al, , 2017 have renewed the interests in this topic and boosted the technology around it. Moving from the phrase-based approaches used in the first editions of the task , last year the multi-source neural models (Chatterjee et al, 2017;Junczys-Dowmunt and Grundkiewicz, 2017;Hokamp, 2017) have shown their capability to significantly improve the output of a PBSMT system. These APE systems shared several features and implementation choices, namely: 1) an RNN-based architecture, 2) the use of large artificial corpora for training, 3) model ensembling techniques, 4) parameter optimization based on Maximum Likelihood Estimation (MLE) and 5) vocabulary reduction using the Byte Pair Encoding (BPE) technique.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the MT output as a source sentence and the post-edited output as a target sentence, this problem can be cast as a monolingual translation task and be addressed with different MT solutions (Simard et al, 2007;Pal et al, 2016). However, it has been proven that better performance can be obtained by not only using the raw output of the MT system but also by leveraging the source text (Chatterjee et al, 2017). In the last round of the APE shared task (Chatterjee et al, 2018a), the top-ranked systems (Tebbifakhr et al, 2018;Junczys-Dowmunt and Grundkiewicz, 2018) were based on Transformer (Vaswani et al, 2017), the state-of-the-art architecture in neural MT (NMT), with two encoders to encode both source text and MT output.…”
Section: Introductionmentioning
confidence: 99%